Exploration of TPACK in IPAS Subjects in Optimizing Digital Literacy of Students with Special Needs - Pramusti, Renanda Ajeng; Ulum, Bahrul; Kumalasani, Maharani Putri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
In the fourth revolution or 4.0 era, known as the digital revolution, there have been many rapid and competitive changes. This change has a huge impact on the world of education, one of which is in elementary school. However, problems often arise during learning activities in the classroom, one of which is the lack of interest in reading or literacy in students with special needs (PDBK). By looking at conditions like this, digital literacy can solve this problem. This study examines the exploration of TPACK in IPAS subjects in optimizing the digital literacy of students with special needs. This research uses a qualitative descriptive method using three data collection techniques, namely observation, interviews, and documentation. The results showed that (1) the technologies used in social studies learning for students with special needs are an interactive map, E-comic, and Google Classroom, (2) the implementation of TPACK for students with special needs, and (3) the advantages of applying digital platforms to students with special needs indicate the increase of the motivation and involvement of students in the learning process. The research results are expected to contribute to the development of technology that is more effective and inclusive for students with special needs. This research can also be a reference for educators in designing learning that is more suitable for students with special needs.